INCLUSIVE CIVIL SOCIETY: ENHANCING ACCESS TO JUSTICE THROUGH COMMUNITY-BASED WITNESS AND VICTIM PROGRAMS - Mulyani, Leni Widi; David, Desiree (LITIGASI, 2023)
Witnesses and victims are crucial elements in the criminal justice system, as their participation aids in uncovering the truth. However, in Indonesia, their protection and support remain inadequate. Many witnesses and victims face intimidation, actual threats, and potential harm. The Indonesian Agency for Witness and Victim Protection (LPSK) was established to safeguard their rights and provide protection. Despite its mandate, LPSK faces significant challenges due to Indonesia's vast territory and increasing caseloads, necessitating collaboration with local communities. To address this, the Friends of Witnesses and Victims (Sahabat Saksi dan Korban—SSK) program was created—a community-based initiative operational in seven regions to bridge the gap between LPSK and affected individuals. This study examines: (1) how community involvement facilitates protection and access to justice for witnesses and victims, and (2) the challenges faced by the SSK program in assisting communities. Using normative legal research, supported by social and conceptual approaches, data was collected through structured interviews with program participants and LPSK implementing teams. Findings reveal that the SSK program significantly enhances LPSK's outreach, providing vulnerable individuals with better access to their legal rights. Simultaneously, it fosters a sense of protection and state recognition within the community. The novelty of this research lies in its exploration of civil society's role in supporting witness and victim protection, highlighting the program’s potential as a scalable model for improving justice accessibility. This study contributes to strengthening community-state cooperation in the field of victim and witness protection in Indonesia.